Disease hot spots of ryanodine receptors - Van Petegem, Filip (Henry Stewart Talks, 2012)
Ryanodine Receptors and calcium release, Disease mutations: malignant hyperthermia and cardiac arrhytmia, Disease hot spots and their locations, High Resolution structures: mutations and domain interfaces, deletion of exon3, Common allosteric mechanisms in IP3 receptors